Evaluation of surface roughness, wettability and adhesion of multispecies biofilm on 3D-printed resins for the base and teeth of complete dentures (Journal of Applied Oral Science, 2024)
Studies evaluating the roughness, wettability and microbial adhesion of 3D-printed resins for complete denture bases and teeth are scarce. Objective: This study evaluated the surface roughness, wettability and adhesion of multispecies biofilms (Candida albicans, Staphylococcus aureus and Streptococcus mutans) on 3D-printed resins for complete denture bases and teeth compared to conventional resins (heat-polymerized acrylic resin; artificial pre-fabricated teeth). Methodology: Circular specimens (n=39; 6.0 mm Ø × 2.0 mm) of each group were subjected to roughness (n=30), wettability (n=30) and biofilm adhesion (n=9) tests. Three roughness measurements were taken by laser confocal microscopy and a mean value was calculated. Wettability was evaluated by the contact angle of sessile drop method, considering the mean of the three evaluations per specimen. In parallel, microorganism adhesion to resin surfaces was evaluated using a multispecies biofilm model. Microbial load was evaluated by determining the number of Colony Forming Units (CFU/mL) and by scanning electron microscopy (SEM). Data were subjected to the Wald test in a generalized linear model with multiple comparisons and Bonferroni adjustment, as well as two-way ANOVA (α=5%). Results: The roughness of the conventional base resin (0.01±0.04) was lower than that of the conventional tooth (0.14±0.04) (p=0.023) and 3D-printed base (0.18±0.08) (p<0.001). For wettability, conventional resin (84.20±5.57) showed a higher contact angle than the 3D-printed resin (60.58±6.18) (p<0.001). Higher microbial loads of S. mutans (p=0.023) and S. aureus (p=0.010) were observed on the surface of the conventional resin (S. mutans: 5.48±1.55; S. aureus: 7.01±0.57) compared to the 3D-printed resin (S. mutans: 4.11±1.96; S. aureus: 6.42±0.78). The adhesion of C. albicans was not affected by surface characteristics. The conventional base resin showed less roughness than the conventional dental resin and the printed base resin. Conclusion: The 3D-printed resins for base and tooth showed less hydrophobicity and less adhesion of S. mutans and S. aureus than conventional resins.